Effects of feed withdrawal on the weight, fecal excretion and Salmonella status of market age broiler chickens. - Rigby, C E (1981)
The withdrawal of feed from the pens of broiler chickens for several hours before they are shipped for slaughter is an increasingly common practice, whose objective is to decrease fecal contamination of birds during processing. In this study, Salmonella typhimurium-infected market age broiler chickens were subjected to feed withdrawal for eight hours, then placed in crates for 18 hours before they were killed and weighed. The intestines, ceca, and cloacal feces were weighed and cultured for salmonellae. The feces deposited in the crates were also weighed and cultured. The results were compared with those of control birds whose feed was not withdrawn before they were placed in crates. The withdrawal of feed did not significantly affect the total liver weights of the birds, but reduced the weights of the intestines in 7/10 groups, and of the ceca in 5/11 groups, and dramatically reduced the amount of feces deposited in the crates. There was no consistent effect on excretion of salmonellae. These results indicated that feed withdrawal for eight hours before broilers are shipped for slaughter should be effective in reducing the spread of fecal contamination and of salmonellae during transport and processing, and in improving the effectiveness of crate washing procedures.